Developing reading comprehension of the English language for UCST students by Flipped Classroom - Omar A. S. Salah (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
This study aimed to reveal the effectiveness of using the strategy of the Flipped Classroom in the development of the reading skills of the English language among the students of the Faculty of Science and Technology (UCST) in Palestine. The researcher relied on the semi -experimental curriculum on a sample of 80 students, which was divided into two groups: experimental studied using the reflected class strategy, and a control in the traditional way. The study included the application of the reading skills test before and after the experiment to measure the effect of the strategy. The results showed that there are statistically significant differences in favor of the experimental group, as the strategy contributed to the development of reading understanding skills (craftsmanship, deductive, critical, and creative) and increasing interaction between students and educational content. The results also demonstrated the effect of students’ learning after a period of the end of the experiment. The study recommended the need to adopt a class strategy reflected in university education and train teachers on it, in addition to developing educational content that supports self -learning and student interaction using modern technology.